2020
DOI: 10.1002/aenm.202001119
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Polyelemental Nanoparticles as Bifunctional Catalysts for Oxygen Evolution and Reduction Reactions

Abstract: Efficient electrocatalysts are critical in various clean energy conversion and storage systems.Polyelemental nanomaterials are attractive as multi-functional catalysts due to their wide compositions and synergistic properties. However, controlled synthesis of polyelemental nanomaterials is difficult due to their complex composition. Herein, we present a one-step synthetic strategy to fabricate a hierarchical polyelemental nanomaterial, which contains ultra-small precious metal nanoparticles (IrPt, ~5 nm) ancho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…11 Löffler et al found that Cr-Mn-Fe-Co-Ni complex solid solution showed at least comparable catalytic activity to Pt in oxygen reduction reaction (ORR), in despite that none of its constituents had good ORR activity. 12 In addition to HEA, other alternative denominations have also been discussed elsewhere, such as complex solid solutions, [12][13][14] multiprincipal element alloys, 15 polyelemental particles, 16,17 multi-elemental alloy, 18 and multimetallic clusters/particles. 19 These kinds of alloys may present a class of promising ideal catalysts having desired activity, stability and selectivity and thus make a paradigm shi in catalysis research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Löffler et al found that Cr-Mn-Fe-Co-Ni complex solid solution showed at least comparable catalytic activity to Pt in oxygen reduction reaction (ORR), in despite that none of its constituents had good ORR activity. 12 In addition to HEA, other alternative denominations have also been discussed elsewhere, such as complex solid solutions, [12][13][14] multiprincipal element alloys, 15 polyelemental particles, 16,17 multi-elemental alloy, 18 and multimetallic clusters/particles. 19 These kinds of alloys may present a class of promising ideal catalysts having desired activity, stability and selectivity and thus make a paradigm shi in catalysis research.…”
Section: Introductionmentioning
confidence: 99%
“…19 These kinds of alloys may present a class of promising ideal catalysts having desired activity, stability and selectivity and thus make a paradigm shi in catalysis research. 20 These alloy catalysts with appealing performances have been reported recently, [10][11][12][17][18][19][21][22][23][24] yet, the interpretation on their properties is still challenging. Quite recently, Rossmeisl and co-authors have made a great step in theoretically predicting ORR 25 and CO 2 and CO reduction 26 properties on HEAs by combing density functional theory calculations and supervised machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…The two peaks with binding energies of 778.7 and 794.1 eV belong to cobalt in Co-FeS 2 . The fitted peaks at 780.9 eV and 797.3 eV can be assigned to cobalt in single-phase CoS 2 [ 25 ]. The two satellite peaks (identified as “Sat”) with binding energies at 784.8 and 803.3 eV are attributed to oxidized Co, produced by the oxidation of the Co-FeS 2 /CoS 2 surface [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Catalyst with single component that works to either ORR or OER is generally unsatisfied to the other reaction. [ 86 ] For example, Pt as the efficient ORR catalyst can be oxidized under OER condition, and OER catalyst, such as Ir‐ or Ru‐based catalyst, is insufficient to ORR. Therefore, it is natural to put forward the concept of exploring bifunctional active catalyst from incorporating multiple targeted components, since formation of polyelemental catalyst can combine the merits of different component.…”
Section: Effects For Interface Engineeringmentioning
confidence: 99%
“…Reproduced with permission. [ 86 ] Copyright 2019, American Association for the Advancement of Science. e) Schematic illustration of metal atom trapped by defect.…”
Section: Interface Engineering Towards Sacsmentioning
confidence: 99%